2010
DOI: 10.1186/1752-4458-4-21
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mental health into primary health care in Zambia: a care provider's perspective

Abstract: BackgroundDespite the 1991 reforms of the health system in Zambia, mental health is still given low priority. This is evident from the fragmented manner in which mental health services are provided in the country and the limited budget allocations, with mental health services receiving 0.4% of the total health budget. Most of the mental health services provided are curative in nature and based in tertiary health institutions. At primary health care level, there is either absence of, or fragmented health servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
49
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 21 publications
12
49
1
1
Order By: Relevance
“…These results were supported by the findings from the study by Chambers et al 32 and Mwape et al, 8 who they found that nurses held positive attitudes towards management of mental health disorders.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…These results were supported by the findings from the study by Chambers et al 32 and Mwape et al, 8 who they found that nurses held positive attitudes towards management of mental health disorders.…”
Section: Resultssupporting
confidence: 75%
“…4 Despite the important role PHC nurses play in the provision of health to the general population, their attitudes towards people with mental illness are often negative, [5][6][7] and provision and identification of mental health problems by PHC nurses has been shown to be poor because their knowledge to deal with mental health conditions is inadequate. 8,9 Many nurses lack knowledge and skills to identify and manage mental health conditions. 10 The World Health Organization (WHO) is of the opinion that training of PHC nurses is effective in improving recognition of mental health disorders in PHC settings.…”
Section: Introductionmentioning
confidence: 99%
“…The unavailability of mental health services in rural communities has left many families with no alternative but to use whatever is available. According to Mwape et al [28] Integrating mental health services into primary health care as a way of facilitating early detection and intervention for mental disorders is critical to improving and promoting the mental health of the population.…”
Section: Discussionmentioning
confidence: 99%
“…The long table approach is a systematic, manual method for organising large amounts of information and identifying themes 11 12…”
Section: Methodsmentioning
confidence: 99%